Residual Class Storage Base For Video Servers. - Haili, Hailiza Kamarul; Sumari, Putra (2005)
Many concepts in number theory have been adopted in various disciplines for problem solving. In this paper a method for data storage scheme in video on demand (VOD) servers is proposed.